EZH2 Promotes T Follicular Helper Cell Differentiation Through Enhancing STAT3 Phosphorylation in Patients With Primary Sjögren’s Syndrome - He, Chengmei; Yang, Yanlei; Chen, Zhilei; Liu, Suying; Lyu, Taibiao; Zeng, Liuting; Wang, Li; Li, Yongzhe; Wang, Mu; Chen, Hua; Zhang, Fengchun (Frontiers in Immunology, 2022)
Objectives Enhancer of zeste homolog 2 (EZH2) is an epigenetic regulator that plays an essential role in immune system development and autoimmune diseases. This study aimed to characterize the role of EZH2 in the pathogenesis of primary Sjögren’s syndrome (pSS). Methods We analyzed EZH2 expression in two transcriptomic datasets of peripheral blood mononuclear cells (PBMCs) from pSS patients and healthy controls. We measured EZH2 expression in CD4+ T cells, CD8+ T cells, and CD19+ B cells from pSS patients and healthy controls and correlated EZH2 expression with clinical parameters. We also examined the activation, proliferation, and T-cell differentiation of CD4+ T cells using the EZH2 inhibitor GSK126, EZH2 siRNA, and EZH2-expressing vector. We further examined the STAT3 signaling pathway after EZH2 inhibition and detected Tfh differentiation in EZH2-overexpressed CD4+ T cells with STAT3 knocked down. Results EZH2 was upregulated in GSE164885 and GSE48378. EZH2 expression was higher in pSS CD4+ and CD8+ T cells, and EZH2 expression in circulating pSS CD4+ T cells was positively correlated with IgG, IgA, ESR, RF, and the circulating Tfh population. EZH2 inhibition and silencing EZH2 suppressed activation, proliferation, and Tfh differentiation. Furthermore, overexpressing EZH2 promoted activation, proliferation, and Tfh differentiation in CD4+ T cells. EZH2 inhibition attenuated STAT3 phosphorylation in CD4+ T cells. STAT3 knockdown abrogated EZH2-promoted Tfh differentiation. Conclusions EZH2 expression was abnormally elevated in pSS CD4+ T cells, which facilitated Tfh differentiation of CD4+ T cells by enhancing STAT3 phosphorylation. EZH2 promotes Tfh differentiation and might be implicated in pSS pathogenesis.